Neutrophil extracellular traps and dsDNA predict outcomes among patients with ST-elevation myocardial infarction - Jing Liu (Nature Portfolio, 2019)
Abstract Neutrophil extracellular traps (NETs) which have a potential role in noninfectious diseases, may play an important role in patients with acute coronary syndrome. The goal of this study was to investigate the association of NETs and in-hospital major adverse cardiac events among patients with ST-segment elevation myocardial infarction (STEMI). Using immunofluorescence staining, ELISA, and fluorescent enzyme standard instrument, we assessed NETs and NETs-related factors. Multivariate analyses were performed after univariate analyses to investigate which variables were independently associated with major adverse cardiac events. Compared with peripheral arteries, we observed neutrophils obtained from infarct-related artery (IRA) releasing NETs. The dsDNA levels, NET-specific marker myeloperoxidase/deoxyribonucleic acid (MPO/DNA) complexes and NETs-related factor tissue factor were significantly higher in coronary plasma samples. Multivariate analysis that white cell counts and coronary dsDNA were independently associated with in-hospital major adverse cardiac events. ROC curve for coronary dsDNA showed sensitivity of 78.0% and specificity of 53% for the cut-off value of 0.39ug/ml. Conclusion, these results provide evidences indicating NETs were associated with STIM, and occurrence of adverse cardiac events.